Using e-learning in teaching and learning cartogram for students of geography - Huynh , Phẩm Dũng Phát (Journal of Technical Education Science, 2011)
Cartogram is a form of map which has been widely used in research, teaching and learning geography in developed countries. The article wishes to introduce to the teachers the way to apply e-learning in the speciality of geoscience